Activity organization and knowledge construction during competitive interaction in table tennis - Sève, C.; Saury, J.; Theureau, J.; Durand, M. (Cognitive Systems Research, 2002)
Using a semiological framework and course-of-action theory, this study analyzes the activity of a top-level table tennis player during a match. Recorded data from an international meet was obtained and then supplemented by verbalization data from a post-match interview. The meaningful units that made up the player`s course of action were labelled so as to: (a) reconstruct the dynamics of the activity as the match took place, (b) point out how the player`s mode of involvement evolved, and (c) determine how knowledge was constructed in action. The player began the match by attempting to discover the particular features of the opponent`s play. This was followed by the reproduction of the effective actions just discovered. The player`s activity during the match did not consist of applying predefined plans, but included exploration, learning, disguising, and indetermination. The results raise the question of the role of practice and training in producing skillful performance.